Bentuk Pemberdayaan Masyarakat Lokal Dalam Pengembangan Desa Wisata Mengesta, Kabupaten Tabanan, Bali - Sayu Putri Newanjani Chelsea; Ida Ayu Suryasih (JURNAL DESTINASI PARIWISATA, 2021)
Developing a village will be beneficial for local communities to empower them in tourism activities. This study is aimed at examining the existing situations of the local communities and analyzing the form of empowering them in Mengesta Tourism Village. Qualitative study with desctiptive analysis technique were utilized in this study. Additionally, the data were gathered by undertaking observation, interview, and documentation. Purposive sampling technique was utilized to determine the informants so that the proper information could be attained. The results demonstrate that the local communities lack their involvement in the empowerment activity in their village. Besides, this empowerment should encompass capital and motivator assistances, including establishing the tourism organizations with hospitality, generating excellent and in-depth communication, and socializing intensively to the entire community, Pokdarwis, and operational managers. Keywords: community empowerment, tourism village